Comparative Analysis of Internal Structure and Functions of Digital Archives Preserving Complex Electronic Records - Stančić, Hrvoje (Array, 2014)
The authors conduct structural and functional analysis of five implemented digital archival systems followed by their comparative analysis. They analyse digital archive implementations in The Federal Chamber of Architects and Engineers - BAIK (Austria), The Agency for Medicinal Products and Medical Devices - HALMED (Croatia), The Braunschweig Clinic (Germany), The Federal Office for Information Security - BSI (Germany), and Lithuanian Office of the Chief Archivist - Electronic Archive Information System - EAIS (Lithuania). The digital archival systems are responsible for preservation of digitised or digital records in the land register (BAIK), classified records on medicines and medical devices granted to the market (HALMED), time- stamped electronic health records (Braunschweig), electronically signed records (BSI), and records of the public administration created as part of governmental e-services and signed by advanced electronic signatures (EAIS). After the structural and functional analysis of each system, they are comparatively analysed according to the criteria grouped around functionalities and system processes, implemented formats and standards, used cryptographic formats, access to the system, and available software tools for management of preserved records. The authors give conclusion on the issues regarding long-term preservation of electronic records having additional preservation requirements due to the time-stamping, addition of (advanced) electronic signatures, and (qualified) certificates in the situations when it is necessary to ensure their authenticity, integrity and non-repudiation.